Peningkatan Literasi Dan Numerasi Melalui Program KKN Outcome Based Education (OBE) di MI Azzainiyah II Karanganyar Paiton - Feriska Listrianti; Rizka Nur Azizah; Hanifa Hadi Kusuma Wardani (Institut Nalanda, 2023)
This research aims to analyze the positive impact of education-based community engagement programs on improving the literacy and numeracy of students at MI Azzainiyah II Karanganyar Paiton. The problem faced by the partner institution is the low proficiency of students in reading, writing, and arithmetic. This program was conducted in the context of the Real Work Lecture (Kuliah Kerja Nyata or KKN) using the Outcome Based Education (OBE) approach as the framework. The community engagement program holds significant importance as it helps address fundamental issues in education at MI Azzainiyah II. The methods employed include improving educational infrastructure and facilities, developing relevant teaching materials, teacher training, and additional learning sessions for students. The program also enhances parental involvement in supporting their children's learning. The research results indicate that after participating in the KKN OBE program, there was a significant improvement in students' literacy and numeracy. A total of 68% of students reported positive changes in their reading interest, while 70% of students noted a positive shift in their interest in Mathematics. These findings underscore the effectiveness of the interactive approach in stimulating student interest and engagement in learning activities. In conclusion, this community engagement program plays a crucial role in enhancing the literacy and numeracy of MI Azzainiyah II students. It emphasizes the importance of collaborative efforts between universities, schools, and communities in improving the quality of education. The positive outcomes provide motivation to continue improvement efforts and ensure the sustainability of the program in the long term.